X-ray scattering by cybotactic nematic mesophases - Azároff, Leonid V. (1980)
A structural model is proposed to account fully for observed x-ray scattering by certain nematic mesophases above their transition to smectic-C phases. In an external magnetic field, the constituent molecules tend to align into nearly periodic parallel chains that give rise to disc-like intensity distributions along the meridian in reciprocal space. Close to the transition temperature, the chains aggregate into parallel sheets which cause a ring-shaped intensity rise in these dises. The planar array in the cybotactic nematic bears a close similarity to that in cholesteric mesophases.